Peningkatan Literasi Teknologi Informasi Bagi Perangkat Kelurahan di Lingkungan Kecamatan Ilir Barat Dua Kota Palembang - Parama Santati; Yulia Saftiana; Hera Febria Mavillinda; Reza Ghasarma (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: to improve information technology literacy of employees in Ilir Barat Dua Subdistrict, Palembang City, especially regarding the use of software applications supporting office administration especially word processing, data processing, and presentation applications in order to improve employee performance. Method: The training was carried out face-to-face, in the form of demonstrations on how to use the menus in each application, questions/answers, and practice using application programs. The target of this activity was the village apparatus in the Ilir Barat Dua District, Palembang City, as many as 36 people. The training was carried out in the Computer Laboratory managed by the Quantitative and Qualitative Laboratory of the Faculty of Economics, Sriwijaya University. Results: After participating in this training, participants realized that this training contributed to improving their skills in using computer applications. Limitations: this activity only covers the use of office administration applications. Other materials should also be given, such as how to find data on the Internet Contribution: after participating in this training, the skills of employees have increased in using of computer applications to support office administration, so that they can contribute to improving employee performance.